American carrier air power at the dawn of a new century - Lambeth, Benjamin S. 1943- (RAND, 2005)
In the Afghanistan war, U.S. carrier-based fighters substituted almost entirely for land-based theater air forces. The Navy's carriers again played a key role in conducting around-the-clock operations against Saddam Hussein's forces in Iraq. American carrier air power is now able to conduct coordinated deep-strike missions well beyond coastal reaches. The Navy's performance over Afghanistan and Iraq showed how the nation's carrier force can provide around-the-clock target coverage, consistently accurate target attack, and multiple successful target attacks per sortie.
Includes bibliographical references
Keywords: United States -- Navy -- Aviation; United States -- Marine Corps -- Aviation; POLITICAL SCIENCE / Political Freedom & Security / General; POLITICAL SCIENCE / Political Freedom & Security / International Security; TECHNOLOGY / Military Science; Aircraft carriers -- United States; Afghan War, 2001- -- Aerial operations, American; Afghan War, 2001- -- Naval operations, American; War on Terrorism, 2001-; Iraq War, 2003- -- Aerial operations, American; Iraq War, 2003- -- Naval operations, American; Terrorismus; Afghanistankrieg -- 2001-2021; Golfkrieg -- 2003; Bekämpfung; Marine; Flugzeugträger; USA